Crystalline phase regulation of anatase–rutile TiO2 for the enhancement of photocatalytic activity. Issue 71 (9th December 2020) - Wang, Kuang; Zhuo, Yan; Chen, Jiayi; Gao, Dawei; Ren, Yu; Wang, Chunxia; Qi, Zhenming
Abstract : Biphasic TiO2 with adjustable crystalline phases was prepared by the hydrothermal-calcination method assisted by nitric acid (HNO3 ) and hydrogen peroxide (H2 O2 ), using potassium titanate oxalate (K2 TiO(C2 O4 )2 ) as the titanium source. Abstract : Biphasic TiO2 with adjustable crystalline phases was prepared by the hydrothermal-calcination method assisted by nitric acid (HNO3 ) and hydrogen peroxide (H2 O2 ), using potassium titanate oxalate (K2 TiO(C2 O4 )2 ) as the titanium source. The influences of H2 O2 volume on anatase and rutile contents and photocatalytic activity of biphasic TiO2 were investigated and the photocatalytic mechanism was explored. X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), UV-vis diffuse reflectance spectroscopy (UV-vis DRS) and specific surface area (BET) were employed to characterize crystal structure, physical morphology, absorbable light, chemical composition, specific surface area and pore size distribution. The photocatalytic degradation efficiency towards a methylene blue (MB) solution under xenon light was tested, and the photocatalytic stability of the sample was investigated by photocatalytic cycle experiments. The prepared biphasic TiO2 was nanorod-shaped and had a large specific surface area. The results showed the anatase TiO2 content increased and the photocatalytic efficiency was enhanced as the H2 O2 volume solution increased. Among the catalysts, the biphasic TiO2 prepared with 30 mL of H2 O2 had the best photocatalytic effect and could entirely degrade the MB solution after 30 minutes under irradiation. After three repeated degradations, the photocatalytic degradation rate was still estimated to be as high as 95%. It is expected that the work will provide new insights into fabricating heterophase junctions of TiO2 for environmental remediation.